Science, (Anti-)Communism and Diplomacy The Pugwash Conferences on Science and World Affairs in the Early Cold War - Kraft, Alison; Sachse, Carola (Brill, 2019)
From 1957 onwards, the "Pugwash Conferences" brought together elite scientists from across ideological and political divides to work towards disarmament. Through a series of national case studies - Austria, China, Czechoslovakia, East and West Germany, the US and USSR - this volume offers a critical reassessment of the development and work of "Pugwash" nationally, internationally, and as a transnational forum for Track II diplomacy. This major new collection reveals the difficulties that Pugwash scientists encountered as they sought to reach across the blocs, create a channel for East-West dialogue and realize the project's founding aim of influencing state actors. Uniquely, the book affords a sense of the contingent and contested process by which the network-like organization took shape around the conferences.